ANALISIS ALGORITMA K-MEANS CLUSTERING UNTUK PEMETAAN PRESTASI SISWA STUDI KASUS SMP NEGERI I SUKAHENING - Ai Ilah Warnilah (LPPM Universitas Bina Sarana Informatika, 2016)
Abstract - The high success rate of students and the low level of student failure is a reflection of the quality of education. Education today are required to have the ability to compete by utilizing all available resources. In addition to resource infrastructure, facilities and people, information systems is one of the resources that can be used to improve the ability to compete. Data mining is the process of analyzing the data to find a pattern of the data set. Data mining is able to analyze a large amount of supporting data into information in the form that has meaning for decision support. One of the clustering process of data mining is one of the methods called k-means. K-Means algorithm is the simplest clustering algorithm than other clustering algorithms. Atribut group student achievement are the Name, extracurricular, value includes the value Skills Knowledge, Attitude value, and the number of absences students. From the results of a case study of 173 students obtained with manhattan distance, chbychep distance euclidian distance the resultaccuracy 67 %.Keywords: Clustering, K-means, student achievementAbstrak - Tingginya tingkat keberhasilan siswa dan rendahnya tingkat kegagalan siswa merupakan cermin kualitas dunia pendidikan. Dunia pendidikan saat ini dituntut untuk memiliki kemampuan bersaing dengan memanfaatkan semua sumber daya yang dimiliki. Selain sumber daya sarana, prasarana dan manusia, sistem informasi merupakan salah satu sumber daya yang dapat digunakan untuk meningkatkan kemampuan bersaing. Data mining merupakan proses analisa data untuk menemukan suatu pola dari kumpulan data. Data mining mampu menganalisa jumlah data yang besar menjadi informasi yang mempunyai arti bagi pendukung keputusan. Salah satu proses data mining adalah clustering. Atribut yang digunakan dalam pengelompokan prestasi siswa adalah nama, ekstrakurikuler, nilai pengetahuan yang meliputi nilai keterampilan, nilai sikap, dan jumlah ketidak hadiran siswa. Studi kasus pada 173 siswa dengan perhitungan jarak menggunakan manhattan distance, chbychep distance dan euclidian distancemenghasilkan akurasi sebesar 67%.Kata Kunci: Clustering, k-means, Prestasi siswa